An application of genetic algorithm and least squares support vector machine for tracing the transmission loss in deregulated power system - Mohd. Herwan, Sulaiman; Siti Rafidah, Abdul Rahim; Mohd Wazir, Mustafa; Hussain, Shareef, Dr.; Saifulnizam, Abd. Khalid, Dr.; Omar, Aliman (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/